Association of cardiovascular health with COPD (NHANES 2007-2020): mediating potential of lean body mass - Gou, Ruoyu; Chang, Xiaoyu; Dou, Danni; Meng, Xin; Hou, Ling; Zhu, Lingqin; Tuo, Wei; Li, Guanghua (Frontiers in Endocrinology, 2025)
BackgroundChronic Obstructive Pulmonary Disease (COPD) is a major global health concern, with lifestyle factors playing a crucial role in its prevention. This study aims to explore the relationship between Life’s Crucial 9 (lc9) scores and COPD odds, and to assess the mediating potential of lean body mass (LBM) in this association.MethodsThis study used cross-sectional study to assess the association between lc9 score and COPD using data from the National Health and Nutrition Examination Survey (NHANES) from 2007 to 2020. Weighted multivariate regression analyses were performed to examine lc9 score on the odds of COPD after adjusting for confounders. The models were adjusted for age, gender, race/ethnicity, Marital status, education level, Family income-to-poverty ratio, LBM and Alcohol consumption status. The discrimination ability of lc9 on COPD odds was evaluated using (ROC) curve. Mediation analysis was used to investigate the mediating potential of LBM between lc9 and COPD odds. Subgroup analyses and interaction assessments were also performed.ResultsIn Model 2, the results showed that for every 10-point change in the lc9 score, the odds of developing COPD decreased. The OR (95% CI) in the Moderate and High groups were OR = 0.37; 95% CI: 0.23, 0.59 and OR = 0.16; 95% CI: 0.09, 0.27 (P for trend < 0.001), respectively. In addition, the results for quartile subgroups were Q3, OR = 0.58; 95% CI: 0.42, 0.81), Q4, OR = 0.24; 95% CI: 0.16, 0.36) and P for trend < 0.001. This relationship was consistent across the total population, subgroup analyses, and sensitivity analyses. There was a nonlinear relationship between lc9 score and odds of COPD (P for Nonlinear = 0.022). The lc9 reduced the odds of COPD by increasing LBM. The lc9 is an suggestive predictor of COPD odds association.ConclusionsHigher LC9 scores, particularly when accompanied by increased LBM levels, showed significant associations with reduced COPD risk in cross-sectional analyses.